Pathway to zero surgical site infections. (1st November 2022) - Low, Daniel
Abstract : Surgical site infections (SSIs) lead to patient morbidity and mortality, have a significant financial impact, and have an indirect impact on the veterinary team. Measures can be taken preoperatively, intraoperatively, and postoperatively to minimise the incidence of SSIs. Individual interventions may not be clinically or statistically significant in themselves. A care bundle approach may be used to drive down rates of SSI. The evidence base is variable and the interventions may apply differently in different healthcare settings; further high-quality veterinary-specific evidence needs to be generated. Human factors and staff culture also play a role in prevention of SSI. The recommendations made in this article come from the evidence and from an advisory board held by Ethicon.